Web-Based Design of a Crime Information System Dashboard at the Musi Rawas Police Station - Syafri Aprudi (Penerbit Jurnal Indonesia, 2022)
The research entitled designing a dashboard of criminal information system at Musi Rawas Police. Research conducted at the Musi Rawas District Police can conclude that the resulting system can make it easier for admins to process criminal data and can make it easier for leaders to find out the level of crime that occurred.